Laclau in the Balkans: Translating “Populist Reason” in an Illiberal Political and Cultural Context - Jovanoski, Igor (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Igor Jovanoski | Игор Јованоски Title (English): Laclau in the Balkans: Translating “Populist Reason” in an Illiberal Political and Cultural Context Title (Macedonian): Лакло на Балканот: Преведувајќи го „популистичкиот ум“ во нелиберален политички и културен контекст Translated by (English to Macedonian): Igor Jovanoski Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 35-63 Page Count: 28 Citation (English): Igor Jovanoski, “Laclau in the Balkans: Translating ‘Populist Reason’ in an Illiberal Political and Cultural Context,” Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017): 35-60. Citation (Macedonian): Игор Јованоски, „Лакло на Балканот: Преведувајќи го ,популистичкиот ум‘ во нелиберален политички и културен контекст“, Идентитети: списание за политика, род и култура, т. 13, бр. 1-2 (зима 2016 - лето 2017): 35-63.